2020
DOI: 10.1016/j.molp.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

YODA-HSP90 Module Regulates Phosphorylation-Dependent Inactivation of SPEECHLESS to Control Stomatal Development under Acute Heat Stress in Arabidopsis

Abstract: Stomatal ontogenesis is a key element of plant adaptation aiming to control photosynthetic efficiency and water management under fluctuating environments 1,2,3 . Development of stomata is guided by endogenous and environmental cues and is tightly coupled to overall plant growth 1,2,3 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 79 publications
(25 reference statements)
2
52
0
1
Order By: Relevance
“…Notably, among the upregulated DEGs in tomato AtCA-YDA lines, there is a relevant number of genes that belongs to a functional category related with translation and protein folding (38.6% of genes), suggesting that the constitutive expression of AtCA-YDA might have an impact on cells reprograming for efficient protein translation. These data might support a function of YDA in the control of translation initiation in plants under biotic stress conditions, as it has been recently described for heat stress through YDA interaction with HSP90.1 protein ( Samakovli et al, 2020 ). The transcriptional reprograming observed in tomato AtCA-YDA lines would explain the enhanced disease resistance observed in the transgenic tomato lines.…”
Section: Discussionsupporting
confidence: 83%
“…Notably, among the upregulated DEGs in tomato AtCA-YDA lines, there is a relevant number of genes that belongs to a functional category related with translation and protein folding (38.6% of genes), suggesting that the constitutive expression of AtCA-YDA might have an impact on cells reprograming for efficient protein translation. These data might support a function of YDA in the control of translation initiation in plants under biotic stress conditions, as it has been recently described for heat stress through YDA interaction with HSP90.1 protein ( Samakovli et al, 2020 ). The transcriptional reprograming observed in tomato AtCA-YDA lines would explain the enhanced disease resistance observed in the transgenic tomato lines.…”
Section: Discussionsupporting
confidence: 83%
“…KIN10 interacts with SPCH in vivo and in vitro. SPCH is a master regulator of stomatal development downstream of a wide range of environmental and hormonal signals [6][7][8][9] . We found that sucrose treatment and overexpression of KIN10 both resulted in the increased levels of SPCH ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The prime regulator linked to the initiation and proliferation of stomatal precursors is the basic helix-loop-helix transcription factor SPEECHLESS (SPCH), which controls hundreds of downstream genes to promote cell division and fate transitions 4,5 . SPCH also integrates a wide range of environmental and hormonal signals to regulate stomatal development [6][7][8][9] .…”
mentioning
confidence: 99%
“…During heat-induced senescence, leaf cells undergo a series of cellular changes including reactive oxygen species (ROS) accumulation, photosynthetic apparatus impairment and cell death (Cui et al 2020;Ivanov et al 2017;Lee et al 2014). Accordingly, plants have developed complex biochemical regulatory mechanisms to response and adapt to heat stress (Samakovli et al 2020;Li et al 2020;Wu et al 2018). However, the underlying genetic and molecular mechanisms are largely unknown.…”
Section: Resultsmentioning
confidence: 99%